2022
DOI: 10.1155/2022/9144673
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics and Failure Mechanism of Granite with Cross Cracks at Different Angles Based on DIC Method

Abstract: The engineering rock mass is generally composed of the rock matrix and structural plane and is an anisotropic inhomogeneous geological body. Accidents such as roof collapse and well caving caused by joint and fissure expansion occur frequently during tunnel excavation and service, resulting in serious casualties and economic losses. It is of great theoretical significance and engineering value to study the fracture mechanism of the jointed rock mass to ensure the stability of the surrounding rock and the safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results indicated that the dynamic strength of the flawed sandstone increased first and then decreased at a given dynamic strain rate. Wu et al [ 23 ] employed wire cutting equipment to prepare rock samples with different crossed cracks and then used an acoustic emission system and digital image correlation technique to study the fracture process of rock samples under uniaxial compression. It was found that the strength of rock samples with a single crack is generally larger than that of samples with cross cracks, and the strength changes when the angle of the crack is in a “V” shape.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the dynamic strength of the flawed sandstone increased first and then decreased at a given dynamic strain rate. Wu et al [ 23 ] employed wire cutting equipment to prepare rock samples with different crossed cracks and then used an acoustic emission system and digital image correlation technique to study the fracture process of rock samples under uniaxial compression. It was found that the strength of rock samples with a single crack is generally larger than that of samples with cross cracks, and the strength changes when the angle of the crack is in a “V” shape.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering rock masses are anisotropic heterogeneous geological bodies with numerous joints (Wu et al 2022). These joints greatly weaken the mechanical properties of the rock mass(Shan and Lai 2019; Shi et al 2015; Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory test research, to study the fracture mechanism of the joined rock mass, Wu et al [15] made rock samples with different cross cracks with wire cutting equipment and studied the failure process of rock samples under uniaxial compression using an acoustic emission system and digital image correlation technology. Zhang et al [16] processed intact granite into prefabricated fractured granite samples with fracture angles of 0, 30, and 45, respectively.…”
Section: Introductionmentioning
confidence: 99%